Legal Protection For Consumers Who Get Expired Products - Siti Nur Yanti Dukalang (Estudiante Law Journal, 2020)
: The purpose of this study is to find out the legal protection for consumers who get expired products. The type of research used was empirical legal research. While the sampling used purposive sampling and data analysis used qualitative research approach. The results of the study showed that legal protection for consumers from the circulation of expired beverages is divided into two a). Preventive legal protections for consumers from the circulation of expired beverages are by giving warnings to business actors, providing guidance to business actors, destroying expired goods or beverage products, monitoring and supervising the circulation of expired beverages so as not to harm consumers. b). Repressive legal protection for consumers from the circulation of expired beverages by conducting inspections on business actors, confiscation, giving sanctions in the form of verbal and written warnings, conducting raids. It is necessary to tighten supervision and guidance for business actors and implement compensation for consumers who have suffered losses. And even tighter monitoring and supervision in small stalls located in remote villages so that no more consumers feel disadvantaged.